Diabetes: Insights into Thyroid Hormones - Shahid Shehzad, Muhammad Naeem, Rasif Khan, Rashed Ali Khan, Saqibah Rehman, Rida Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Numerous physiological and pathological processes must be controlled for the thyroid gland to function properly. Research utilising both animal models and human subjects has demonstrated that thyroid hormones regulate cellular processes that are crucial for most age-related diseases. Furthermore, both hyperthyroidism and hypothyroidism have been associated to the onset of several kinds of diabetes, proving the intricacy of the molecular processes regulated by thyroid hormones. In this article, we provide a summary of the most recent thyroid hormone-related findings in the field of diabetes research. We contend that despite the difficulty in developing thyromimetics due to their inefficiency and potential toxicity, therapies based on the use of modulators of thyroid hormone activity may be therapeutically beneficial in some kinds of diabetes.